Web Based Nursing Information System to Support Learning - Romi Hendr; Yodhi Yuniarthe; M.Budi Hartanto (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Nursing Information System as an application to improve knowledge and quality in supporting nursing student learning at the health faculties of Indonesian partner universities. The integration of computer science and health sciences to support knowledge is a unique collaboration in supporting this activity. Describe a web-based nursing information system in supporting nursing student learning at the health faculty of Indonesian partner universities. The method used in writing this study is a literature review. Journals and articles related to technology nursing with the title according to the research. Web Based Nursing Information System to Support Nursing Student Learning at the Faculty of Health, Universitas Mitra Indonesia. Can be a solution in increasing knowledge for nursing students in learning on a website-based nursing information system.